Modeling SARS-CoV-2 antibody seroprevalence and its determinants in Ghana: A nationally representative cross-sectional survey. - Irene Owusu Donkor; Sedzro Kojo Mensah; Duah Dwomoh; Jewelna Akorli; Benjamin Abuaku; Yvonne Ashong; Millicent Opoku; Nana Efua Andoh; Jeffrey Gabriel Sumboh; Sally-Ann Ohene; Ama Akyampomaa Owusu-Asare; Joseph Quartey; et al. (PLOS Global Public Health)
Estimates of SARS-CoV-2 transmission rates have significant public health policy implications since they shed light on the severity of illness in various groups and aid in strategic deployment of diagnostics, treatment and vaccination. Population-based investigations have not been conducted in Ghana to identify the seroprevalence of SARS-CoV-2. We conducted an age stratified nationally representative household study to determine the seroprevalence of SARS-CoV-2 and identify risk factors between February and December 2021. Study participants, 5 years and older regardless of prior or current infection COVID-19 infection from across Ghana were included in the study. Data on sociodemographic characteristics, contact with an individual with COVID-19-related symptoms, history of COVID-19-related illness, and adherence to infection prevention measures were collected. Serum obtained was tested for total antibodies with the WANTAI ELISA kit. The presence of antibodies against SAR-COV-2 was detected in 3,476 of 5,348 participants, indicating a seroprevalence of 67.10% (95% CI: 63.71-66.26). Males had lower seroprevalence (65.8% [95% CI: 63.5-68.04]) than females (68.4% [95% CI: 66.10-69.92]). Seroprevalence was lowest in >20 years (64.8% [95% CI: 62.36-67.19]) and highest among young adults; 20-39 years (71.1% [95% CI 68.83,73.39]). Seropositivity was associated with education, employment status and geographic location. Vaccination status in the study population was 10%. Exposure is more likely in urban than rural areas thus infection prevention protocols must be encouraged and maintained. Also, promoting vaccination in target groups and in rural areas is necessary to curb transmission of the virus.